The Role of Canonical Ruler in Transformation of Hadd to Ta’azir Punishments - Hekmatnezhad, Farzad; Raei, Masoud; Panjepour, Javad (Cuestiones Políticas, 2020)
In the Islamic perspective the ruler is a consummate jurisprudent with special authority. In criminal matters, for example, the ruler also has a prominent role, such as setting limits (Hadd) to accepted behaviors and punishments for reprehensible behaviors. In fact, in the case of convenience and special circumstances, the ruler can disapprove or modify a certain punishment. The objective of the article is then to analyze the role of the canonical ruler in the transformation of limit punishments or corporal punishment (tazir) in Iran. Based on the descriptive ـ analytical method, the work concludes that, according to the belief concerning the permission to implement the limits during the time of The Absence, the basic principle is the lack of permission to switch the limits. But if the religious ruler realizes that the implementation of the limits, in certain circumstances, is contrary to the application objectives, the interests of Islamic society and the maintenance of the government, or in the confrontation with certain rules, such as “ to be ashamed ”(لاحرج) and“ without harm ”(لاضرر), he can rule to commute the sentence.